Bi- Level Optimization of Multi-Microgrids: A Review Considering Demand Response Aggregators - Adel Ridha Othman; Ziyodulla Yusupov; Muhammet Tahir Guneser (Journal of Electronic Voltage and Application, 2025)
The increased penetration of renewable energy sources (RES) and electric vehicles (EVs) in addition to the non- renewable energy sources such as microturbine (MT), combined heat and power (CHP) and diesel generator (DEG) must have a coordinated operation for achieving optimal energy management system (EMS) and operation of microgrids. The demand side management (DSM) can be utilized using demand response program (DRP) becomes an essential work to deal with distributed generation (DG) that are integrated with distribution grid to minimize the cost of operation and maximizing the profit of microgrids owners (MGO), this can be achieved by exchanging data between MGO and distribution system operator (DSO). The optimal operation of microgrid is subject to various constraints that must not be violated. The complication of the energy management is due to the uncertainties of RES, electricity prices and EVs state of charge (SoC) and arrival/departure time, have to be solved with a stochastic based modeling. The demand response aggregator (DRA), electric vehicles aggregator (EVA) and energy storage system (ESS) are an important player in microgrid optimization that have to be studied thoroughly as they participate in DSM to modify the load demand pattern. The review assists the authors to find the latest achievements in microgrids management.